Using ecological momentary assessment to examine interpersonal and affective predictors of loss of control eating in adolescent girls. Issue 7 (21st July 2014) - Ranzenhofer, Lisa M.; Engel, Scott G.; Crosby, Ross D.; Anderson, Micheline; Vannucci, Anna; Cohen, L. Adelyn; Cassidy, Omni; Tanofsky‐Kraff, Marian; Weissman, Ruth Striegel; Klump, Kelly; Steiger, Howard; Tanofsky‐Kraff, Marian
ABSTRACT Objective Pediatric loss of control (LOC) eating is predictive of partial‐ and full‐syndrome binge eating disorder. The interpersonal model proposes that LOC eating is used to cope with negative mood states resulting from interpersonal distress, possibly on a momentary level. We therefore examined temporal associations between interpersonal problems, negative affect, and LOC eating among overweight adolescent girls using ecological momentary assessment (EMA). Method Thirty overweight and obese (≥85th body mass index (BMI) percentile; BMI: M = 36.13, SD = 7.49 kg/m2) adolescent females (Age: M = 14.92, SD = 1.54 y; 60.0% African American) who reported at least two LOC episodes in the past month completed self‐report momentary ratings of interpersonal problems, state affect, and LOC eating for 2 weeks. A series of 2‐level multilevel models with centering within subjects was conducted. Results Between‐ and within‐subjects interpersonal problems (p's < .05), but not between‐ (p = .12) or within‐ (p = .32) subjects negative affect predicted momentary LOC eating. At the between‐subjects level, interpersonal problems significantly predicted increases in negative affect (p < 001). Discussion Naturalistic data lend support to the predictive value of interpersonal problems for LOC eating among adolescents. Interventions targeting interpersonal factors on a momentary basis may be useful during this developmental stage. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:748–757)